Modified Brief Cognitive Screening Battery - Indonesian Version: cross-cultural adaptation and normative data based on demographic factors in North Sumatra, Indonesia - Fitri, Fasihah Irfani; Naci, Lorina; Turana, Yuda; Rambe, Aldy Safruddin; Nazriani, Dina; Nitrini, Ricardo; Caramelli, Paulo (Frontiers in Neurology, 2024)
Introduction:. Key component of early detection of dementia is a brief and culturally appropriate cognitive screening tool. This study aimed to perform a cultural adaptation of the Brief Cognitive Screening Battery (BCSB) and to obtain normative data from the older adult population. Methods:Cross-cultural adaptation process to develop BCSB-INA was performed. This was followed by a feasibility study from community dwelling older adults from several urban and rural areas in North Sumatra, Indonesia. Results: The BCSB-INA was generally well understood and showed not much discrepancy in translation from the original version. There were differences in semantic and phonemic fluency and CDT based on years of education, but no difference was found on other domain, including the delayed recall of the FMT. The battery was more influenced by age than education. Discussion:The BCSB-INA is culturally appropriate and feasible to be used in population with heterogenous educational background in Indonesia.